Re-emergence of invasive pneumococcal disease (IPD) and increase of serotype 23B after easing of COVID-19 measures, Switzerland, 2021 - Carlo Casanova; Marianne Küffer; Stephen L. Leib; Markus Hilty (Emerging Microbes and Infections)
Incidence of invasive pneumococcal disease (IPD) has been low during the peak of the COVID-19 pandemic. In this study, we found that the IPD numbers again increased in Switzerland during the first six months of 2021 and that this coincides with the loosening of COVID-19 measures. Vaccine pneumococcal serotypes have continued to decrease and non-vaccine type serotype 23B has emerged (8% of the isolates in 2021). Worryingly, serotype 23B is associated with reduced susceptibility to penicillin.